2021
DOI: 10.1093/geroni/igab046.045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an eLearning Memory Program on Reducing Negative Impact of Age-Related Memory Changes

Abstract: Age-related memory changes pose considerable concerns for aging adults, and can adversely affect their daily living and cause worry even when changes experienced are not clinically significant. The Memory and Aging Program® is a validated psychoeducation and memory strategy-training program that teaches the public about memory changes during aging and trains them to use evidence-based strategies to support brain health. The program has been offered in-person for over 20 years, and a self-guided eLearning versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of cognitive intervention, past work has found that task-specific strategies can mediate experimental task performance in individuals with memory impairment (D'Angelo et al, 2015;Ryan et al, 2013) and these findings, albeit correlational, support that this is also likely occurring in typical aging. Cognitive rehabilitation or intervention programs which teach internal memory strategies to individuals may also benefit from measuring taskspecific strategy use as a treatment or process outcome, instead of self-report or objective task performance, which do not always show effects at program follow-up (Zhu et al, 2021). Furthermore, strategy-based interventions program may consider adding monitoring of strategy use during experimental tasks to their protocols, as is done in metacognitive programs such as Goal Management Training (Stamenova & Levine, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cognitive intervention, past work has found that task-specific strategies can mediate experimental task performance in individuals with memory impairment (D'Angelo et al, 2015;Ryan et al, 2013) and these findings, albeit correlational, support that this is also likely occurring in typical aging. Cognitive rehabilitation or intervention programs which teach internal memory strategies to individuals may also benefit from measuring taskspecific strategy use as a treatment or process outcome, instead of self-report or objective task performance, which do not always show effects at program follow-up (Zhu et al, 2021). Furthermore, strategy-based interventions program may consider adding monitoring of strategy use during experimental tasks to their protocols, as is done in metacognitive programs such as Goal Management Training (Stamenova & Levine, 2018).…”
Section: Discussionmentioning
confidence: 99%